Role of miR-199a-5p in the post-transcriptional regulation of ABCA1 in response to hypoxia in peritoneal macrophages - Aranda, Juan Francisco; Pérez-García, Ana; Torrecilla-Parra, Marta; Fernández-de Frutos, Mario; Martín-Martín, Yolanda; Mateos-Gómez, Pedro A.; Pardo-Marqués, Virginia; Busto, Rebeca; Ramírez, Cristina M. (Frontiers in Cardiovascular Medicine, 2022)
Hypoxia is a crucial factor contributing to maintenance of atherosclerotic lesions. The ability of ABCA1 to stimulate the efflux of cholesterol from cells in the periphery, particularly foam cells in atherosclerotic plaques, is an important anti-atherosclerotic mechanism. The posttranscriptional regulation by miRNAs represents a key regulatory mechanism of a number of signaling pathways involved in atherosclerosis. Previously, miR-199a-5p has been shown to be implicated in the endocytic and retrograde intracellular transport. Although the regulation of miR-199a-5p and ABCA1 by hypoxia has been already reported independently, the role of miR-199a-5p in macrophages and its possible role in atherogenic processes such us regulation of lipid homeostasis through ABCA1 has not been yet investigated. Here, we demonstrate that both ABCA1 and miR-199a-5p show an inverse regulation by hypoxia and Ac-LDL in primary macrophages. Moreover, we demonstrated that miR-199a-5p regulates ABCA1 mRNA and protein levels by directly binding to its 3’UTR. As a result, manipulation of cellular miR-199a-5p levels alters ABCA1 expression and cholesterol efflux in primary mouse macrophages. Taken together, these results indicate that the correlation between ABCA1-miR-199a-5p could be exploited to control macrophage cholesterol efflux during the onset of atherosclerosis, where cholesterol alterations and hypoxia play a pathogenic role.